IL-15-Activated CD38+HLA-DR+CD8+ T cells induce liver injury in cirrhosis via JAK/STAT5 and PI3K/mTOR pathways - Ke Liu; Hongliang Dong; Kaiyue Zhang; Wanping Yan; Huanyu Wu; Jing fan; Wei Ye (Scientific Reports)
Abstract The development and progression of liver cirrhosis are considerably influenced by immune processes, with CD8 + T cells playing a key role. Notably, cytokines can activate bystander CD38 + HLA-DR + CD8 + T cells without the need for T cell receptor (TCR) stimulation. However, their role in liver fibrosis remains controversial. This study aimed to investigate the pathological role of CD38 + HLA-DR + CD8 + T cells in cirrhosis progression and explore the mechanisms that regulate their functions. Peripheral blood mononuclear cells (PBMCs) were extracted from patients with cirrhosis and healthy donors, and the ratio of CD38+HLA-DR+CD8+ T cells was assessed through flow cytometry. The relationship between the prevalence of these cells and certain clinical indicators was investigated. Additionally, CD8+ T cells from healthy donors were used to examine the impact of cytokine IL-15 on CD38+HLA-DR+CD8+ T cells, utilizing flow cytometry and in vitro cytotoxicity assays. Finally, the signaling pathways involved in IL-15 activation of CD38+HLA-DR+CD8+ T cells were examined in vitro. The proportion of CD38+HLA-DR+CD8+ T cells was significantly increased in patients with cirrhosis compared to healthy donors and exhibited a strong correlation with disease severity, hepatic damage, and inflammation in cirrhosis. IL-15-stimulated CD38+HLA-DR+CD8+ T cells from healthy donors demonstrated proliferation and overexpression of cytotoxic molecules, exhibiting NKG2D- and FasL-dependent innate-like cytotoxicity without TCR activation. Notably, IL-15 did not alter the mitochondrial function of these cells. The JAK/STAT5 and PI3K/mTOR pathways were found to play a critical role in IL-15-induced innate-like cytotoxicity. These findings suggested that CD38+HLA-DR+CD8+ T cells from patients with cirrhosis contribute to immune-mediated liver injury. Furthermore, the JAK/STAT5 and PI3K/mTOR pathways were essential for IL-15-induced activation of CD38+HLA-DR+CD8+ T cells, which expressed NKG2D and FasL, demonstrating innate cytotoxicity independent of TCR engagement.